SURAT-SURAT PERJANJIAN TANAH NAGARA AGUNG KARATON NGAYOGYAKARTA TAHUN 1827-1831: SEBUAH KAJIAN FILOLOGI HISTORIS - Agusta, Rendra (Balai Pelestarian Kebudayaan Wilayah X, 2019)
The agreement to divide the Mataram region after the Giyanti agreement still leaves a long problem, especially in areas outside the capital. After the Java war in 1830, areas in the Yogyakarta and Surakarta regions were reorganized by the Dutch East Indies government commissioner. The division gave birth to several derivative agreements, one of which was related to land agreements. The research was a textual study of Pengetan Kagungan Dalem Siti Dhusun from Karaton Surakarta. This research was conducted because this manuscript is a single manuscript or codex unicus which became the basis for the study of the Kraton Surakarta in 19th century. This paper also stores data related to rural ecology in terms of structure, area and tax burden. The research uses the philological method to present text descriptions and editions. Then use content analysis to reveal the contents of the land agreement. This manuscript contains the results of the land ratification of treaties Dutch government related to the management of the Nagara Agung agreed by Sultan Hamengkubuwono V in Yogyakarta and Sunan Pakubuwono VII in Surakarta.